Stretch and/or oxygen glucose deprivation (OGD) in an in vitro traumatic brain injury (TBI) model induces calcium alteration and inflammatory cascade - Salvador, Ellaine; Burek, Malgorzata; Foerster, Carola Y. (Frontiers in Cellular Neuroscience, 2015)
The blood-brain barrier (BBB), made up of endothelial cells of capillaries in the brain, maintains the microenvironment of the central nervous system. During ischemia and traumatic brain injury (TBI), cellular disruption leading to mechanical insult results to the BBB being compromised. Oxygen glucose deprivation (OGD) is the most commonly used in vitro model for ischemia. On the other hand, stretch injury is currently being used to model TBI in vitro. In this paper, the two methods are used alone or in combination, to assess their effects on cerebrovascular endothelial cells cEND in the presence or absence of astrocytic factors. Applying severe stretch and/or OGD to cEND cells in our experiments resulted to cell swelling and distortion. Damage to the cells induced release of lactate dehydrogenase enzyme (LDH) and nitric oxide (NO) into the cell culture medium. In addition, mRNA expression of inflammatory markers interleukin (IL)-6, IL-1α, chemokine (C-C motif) ligand 2 (CCL2) and tumor necrosis factor (TNF)-α also increased. These events could lead to the opening of calcium ion channels resulting to excitotoxicity. This could be demonstrated by increased calcium level in OGD-subjected cEND cells incubated with astrocyte-conditioned medium. Furthermore, reduction of cell membrane integrity decreased tight junction proteins claudin-5 and occludin expression. In addition, permeability of the endothelial cell monolayer increased. Also, since cell damage requires an increased uptake of glucose, expression of glucose transporter glut1 was found to increase at the mRNA level after OGD. Overall, the effects of OGD on cEND cells appear to be more prominent than that of stretch with regards to TJ proteins, NO, glut1 expression and calcium level. Astrocytes potentiate these effects on calcium level in cEND cells. Combining both methods to model TBI in vitro shows a promising improvement to currently available models.